2016
DOI: 10.1021/acs.biomac.6b00766
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent PEGylation via Lectin–Glycopolymer Interactions

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 70 publications
4
33
0
Order By: Relevance
“…One of the first reports addressing the adsorption of PEG chains by Malmsten et al has shown, however, that the protein rejecting capacity of physically adsorbed PEG chains is similar to the efficient protein rejection at sufficiently high chain density of covalently grafted PEG layers. [18] It is worth mentioning that theoretical approaches to describe the effect of modulating size and grafting density of PEG on the plasma adsorption behavior of PEGylated surfaces are in concordance with experimental studies. In general, this method would allow for incorporation of glycol-PEG functionalities in proteins with an engineered sugar-binding site.…”
Section: Introductionsupporting
confidence: 54%
“…One of the first reports addressing the adsorption of PEG chains by Malmsten et al has shown, however, that the protein rejecting capacity of physically adsorbed PEG chains is similar to the efficient protein rejection at sufficiently high chain density of covalently grafted PEG layers. [18] It is worth mentioning that theoretical approaches to describe the effect of modulating size and grafting density of PEG on the plasma adsorption behavior of PEGylated surfaces are in concordance with experimental studies. In general, this method would allow for incorporation of glycol-PEG functionalities in proteins with an engineered sugar-binding site.…”
Section: Introductionsupporting
confidence: 54%
“…Non-covalent polymer-protein binding studies, sometimes involvingd elivery experiments, is ab road field, and additional reports relatedt ot his topic that highlight various binding interactions and characterization methods can be found in Refs. [58][59][60][61][62][63][64][65][66][67][68][69][70][71].B inding studies showcasing availablet echniques could potentially contain criticali nformation necessary for future protein-delivery optimization studies and should not be overlooked.…”
Section: Other Non-covalent Protein-basedcomplexes For Deliverymentioning
confidence: 99%
“…Although the exact mechanism of this interaction remains unknown, numerous studies have demonstrated that the mechanism is highly specic and noncovalent. 34 Thus, an in vitro evaluation of this specic binding event provides an initial test of the ability of a synthetic Gluco-ONB-P(aN 3 CL-g-PONBIMC) 10 polymer to interact with the biological systems, such as in drug delivery development, tissue engineering, and biomedical material synthesis. These tests are typically conducted by mixing Gluco-ONB-P(aN 3 CL-g-PONBIMC) 10 with a lectin that is selective for the sugar conjugated to the polymer.…”
Section: Carbohydrate-lectin Binding Recognitionmentioning
confidence: 99%